MODEL PENGELOLAAN SUMBERDAYA ALAM KELAUTAN DENGAN PENDEKATAN SOSIAL EKONOMI - Ridwan, Mochamad; Gunawan, Romi (Jurnal AGRISEP, 2019)
This study aims to analyze determinants of management optimization level and build a model relating to the management of marine natural resources/capture fisheries with social economic approach in Bengkulu Province. The types of data collected in this study include primary data (as the main data) and secondary data (as supporting data), which arecarried out by interview, questionnaire, focus group discussion, and documentationmethod. The data analysis method used isdescriptive methoanddiscriminant analysismethod.The results showed that through discriminant analysis method, a mathematical (quantitative) model was produced, namely optimizationlevelof marine natural resourcesmanagement, which was significantly determined by 6 (six) determinantfactorsincluding the development of marine natural resource capture method,quality of facilities in TPI(FishMelting Place), quality of togetherness/participation in marine resource management, quality of ability to market of fish catches, role of local customary institution, and role of government institutions (DKP and OPD related).